2011
DOI: 10.1108/14635781111112756
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity risk exposure for specialised and unspecialised real estate banks

Abstract: PurposeThe purpose of this paper is to compare banks specialised on real estate lending with the overall market in order to the test if they are more or less exposed to liquidity risk.Design/methodology/approachFollowing the approach proposed by the Basel Committee in order to evaluate the bank liquidity exposure, the paper compares the value of these measures between the real estate lending banks (REBs) and all other banks for the Italian market. A panel regression analysis is also performed in order to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…Short-term bank credit used by firms is found positively related to TCU. The findings of this study support the complementary hypothesis of trade credit proposed by Burkart and Ellingsen (2004) and are consistent with the evidence reported by previous studies (Agostino & Trivieri, 2014;Giannotti, Gibilaro, & Mattarocci, 2011). Furthermore, results revealed that of financial characteristics 1 of LMFs used as a control variables that have significant impact on trade credit financing used by LMFs.…”
Section: Regression Analysis and Discussionsupporting
confidence: 91%
“…Short-term bank credit used by firms is found positively related to TCU. The findings of this study support the complementary hypothesis of trade credit proposed by Burkart and Ellingsen (2004) and are consistent with the evidence reported by previous studies (Agostino & Trivieri, 2014;Giannotti, Gibilaro, & Mattarocci, 2011). Furthermore, results revealed that of financial characteristics 1 of LMFs used as a control variables that have significant impact on trade credit financing used by LMFs.…”
Section: Regression Analysis and Discussionsupporting
confidence: 91%
“…They show that there exist positive relationships between NSFR and indicators of performance which were return on equity (ROE), return on assets (ROA) and net interest margin (NIM). Other studies include those of Giannotti et al (2011), Angora, and Roulet (2011) and Giordana, and Schumacher (2012.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ogol (2011) on the other hand investigates liquidity risk management practices in microfinance institutions in Kenya using a descriptive research design. Unlike other studies in this area, (Giannotti et al, 2011;Angora & Roulet, 2011;Giordana & Schumacher, 2012), The studies on liquidity in Kenyan commercial banks studies do not consider NSFR and only one considers LCR. These variables are the two dependent variables considered by this study, and are the two liquidity measures proposed in the Basel III framework.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For each operational risk factor, based on analysis of a sample of real estate evaluations conducted by independent valuation companies (data available at December 2018), the following intervals of "standard" values for each differential have been drawn up [40][41][42][43][44][45]:…”
Section: Methodology For the Construction Of The Profitability Index mentioning
confidence: 99%